(untitled) (Academia Science Repository, 2023)
We observed 40 lactating women who had undergone physiological childbirth. Restoration of menstrual function after normal childbirth in nursing mothers after 1.5-5 months occurs in 60% of cases. Lactational amenorrhea for 6-12 months or more after normal delivery occurs in 27.5% of women. The high incidence (27.5%) of unplanned pregnancies in nursing mothers during the first year after normal childbirth indicates the need to use contraceptives immediately after childbirth.